Molecular Detection of Hemagglutinin Gene Fragment of Avian Influenza Virus H9 Subtype Obtained from Poultry Commercial Farm with Prominent Symptom of Decreased Egg Production - Niken Respati Maharani; Heru Susetya; Michael Haryadi Wibowo (Bogor Agricultural University, Indonesia, 2022)
Avian influenza virus H9N2 subtype is considered a low pathogenic strain that has been reported in Indonesia since late 2016. The outbreak has caused economic losses for farmers due to the sharp drop in egg production. The evidence of the existence of AIV H9N2 has been published, but very limited information on the prominent symptom and macroscopic lesion. This research was a retrospective study of suspected avian influenza H9 subtype, obtained from layer commercial farm with recorded characteristic symptoms. Specific trachea samples were collected and further processed to be isolated, propagated using embryonated chicken egg, and then extracted the RNA for molecular detection using real-time reverse transcriptase-polymerase chain reaction (RT-qPCR). A positive result was further detected in its H-9 gene with RT-PCR technique and sequencing methods. One of five samples showed positive for RT-qPCR with CT value 30.19. Sequence analysis confirmed that the sample with characteristic macroscopic lesion could be detected in the presence of the AIV H9 subtype. Phylogenetic tree analyses revealed that this virus belongs to the China-Vietnam- Indonesia (CVI) lineage.